2016
DOI: 10.1103/physrevd.94.105009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Casimir effect withδδmirrors

Abstract: We calculate the spectrum and the total rate of created particles for a real massless scalar field in 1 + 1 dimensions, in the presence of a partially transparent moving mirror simulated by a Dirac δ − δ ′ point interaction. We show that, for this model, a partially reflecting mirror can produce a larger number of particles in comparison with a perfect one. In the limit of a perfect mirror, our formulas recover those found in the literature for the particle creation by a moving mirror with a Robin boundary con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The further generalization to the δ − δ potential was considered in [170]. In this model, the reflection and transmission coefficients have the form…”
Section: Partially Transparent Mirrors and General Boundary Conditionmentioning
confidence: 99%
“…The further generalization to the δ − δ potential was considered in [170]. In this model, the reflection and transmission coefficients have the form…”
Section: Partially Transparent Mirrors and General Boundary Conditionmentioning
confidence: 99%
“…Notably, Moore [41], DeWitt [42], and later on, Davies and Fulling [38,39] initiated a program using field theories with external conditions, which eventually demonstrated that quantities like the expectation values of the stress-energy tensor, and the localization of particles using wave packets, can be calculated in various physical problems and used to extract significant physical consequences of the quantum fields. Indeed, there has been renewed interest [23,24,[43][44][45][46][47][48][49][50][51][52][53][54] in the moving mirror model in recent years due, in part, to claims of experimental verification of the dynamical Casimir effect [55,56]. In many of these particle production scenarios, various systems that exploit the simple mathematical set up of the (1+1)-dimensional moving mirror model have led to novel experimental designs.…”
Section: Introduction: Some Puzzles With Moving Mirrors and Evaporatimentioning
confidence: 99%
“…In this manner it is consistent to take the 0-hit function to be the free space propagator, K 0 (y, x; T ). Through direct substitution we can now write the propagator (12) in a perturbative series that involves successive hit functions integrated over S K(y, x; T ) = K 0 (y, x; T ) − λ…”
Section: Quantum Propagation and The N-hit Functionmentioning
confidence: 99%
“…This is the case, for example, for many scattering problems and contact interactions [7][8][9] and varied models of lattice structure in condensed matter [10,11]. In the relativistic case, constrained path integrals arise in the context of the Casimir effect where one is interested in trajectories that touch the conducting plates [12][13][14][15], and for Dirichlet boundary conditions imposed in some spatial region [16][17][18][19][20][21][22][23][24][25] where the contributions from paths passing through this region should be removed. A fresh approach to calculating, either analytically, approximately or numerically, such path integrals will therefore find wide application.…”
Section: Introductionmentioning
confidence: 99%